Is Anyone Listening? Citizen Participation and The Illusion of Democracy in A Peru Regional Government - Montoro, Ronald Ivan Vasquez (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
This research examines the link between citizen participation and public decision-making in an entity of the public sector in the province of Paita in Peru, in 2024. The research is based on the premise that democratic governance, good public administration, and sustainable development require the involvement of citizens. The research has a non-experimental, descriptive, quantitative design. Information was obtained from questionnaires and interviews of 200 citizens and 40 municipal officials. The research analyzes citizens' participation and the decision-making process, and their dimensions, in the light of commitment, surveillance, and oversight, in the case of participation; and immediate response, effective decisions, and resolution of difficulties, in terms of decision-making. The results suggest that the citizens are "participating the most on average." Officials’ decision-making is also considered, overall, to be largely medium. The trends in citizen participation and determining dimensions are similar, with the majority of scores falling into the middle range. The study underscores the imperative to enhance participatory governance through strengthened communication channels, digital engagement tools, and institutional mechanisms that facilitate collective action. By shedding light on the lived realities of municipal administration in a non-centralized, Global South context, the research offers critical insights for the design of inclusive and responsive public policies. These findings contribute to broader discussions on democratic innovation and the reconfiguration of citizen–state relations in public service delivery.